الإغتراب الوظيفي وأثره على الثقة التنظيمية دراسة حالة صندوق التأمينات الإجتماعية الأغواط - زياني راية; فرحات حميدة (جامعة عمار ثليجي الاغواط, 2022)
This study aims to measure and analyse the impact of job expatriation on organizational confidence that brought to the attention of the employees of the National Social Security Fund in the state of Agouat. The elements of the study were identified by an independent variable of job alienation and a subordinate variable of organizational confidence. To achieve the study's main objective, the analytical descriptive curriculum was used and to gather preliminary information. A questionnaire was designed and distributed to the study's 51 institutional sample of 476 workers using the statistical processing method of the SPSS, in order to verify the study hypotheses. The study found no statistical effect of job expatriation on trust.